Discourse analysis of Joko Widodo's last state of the nation address 2024 - YENIS CONTESA; Surwandono (Faculty of Communications Science, Dr. Soetomo University, 2024)
In a dynamic political context, presidential speeches are crucial in shaping public perception and guiding policy. President Joko Widodo's latest speech on August 16, 2024 that was uploaded through the Presidential Secretariat's YouTube channel, has come under scrutiny for containing important elements relating to communication strategies and leadership legitimacy. This study aims to analyse the speech by exploring how Jokowi's distinctive rhetoric reflects his role in the political agenda. Using a qualitative approach and Van Dijk's critical discourse analysis technique, this study employs a socio-cognitive framework to guide the analysis. Lingual data was collected through free listening techniques, including transcription, observation, and research subject determination. Meanwhile, non-lingual data was obtained from credible news documents and analysed using hermeneutics and phenomenology methods. The results showed that Jokowi built his image as a responsive and effective leader through language that highlighted the successes and challenges of his leadership and built leadership authority by presenting himself as a skilful, strategic, and reality-based leader. This research contributes to understanding rhetorical strategies in political communication and leadership authority studies, with far-reaching implications for public perception and political dynamics.